Rancangan Bangun Smart Home Untuk Deteksi Dini Kebakaran Mengunakan Mikrokontroler Berbasis Android - Pranto Suwarno; Imam Suharjo (Universitas Mercu Buana Yogyakarta, 2022)
Along with the times and the increasing era of technology, the demand for safe, comfortable and modern homes is increasing rapidly, and the technology that is currently in high demand by people is IoT (Internet of Think), IoT allows users to control and monitor the state of their home. Because of its usefulness, the purpose of this research is to produce asystem design smart home combined with this detection feature for fires in the house. The technology applied is in the form of full control and monitoring of temperature and humidity, lighting control, fire detection, and gas leak detection.